The Impact of Human Development Index, Minimum Wage, Labor Force Participation Rate, and Open Unemployment Rate on Economic Growth - Irawan, Toni; Khoirudin, Rifki (Journal of Management Studies and Development, 2024)
This research aims to identify factors influencing the economic growth of Bali Province. The dependent variable used is economic growth, while the independent variables include the Human Development Index, Provincial Minimum Wage, Labor Force Participation Rate, and Open Unemployment Rate. The research employs a quantitative method, utilizing panel data regression with the Random Effect Model (REM). The findings reveal that the Open Unemployment Rate and Provincial Minimum Wage variables significantly and negatively impact economic growth. Conversely, the Labor Force Participation Rate  variable significantly and positively influences economic growth. However, the Human Development Index variable does not demonstrate a significant impact and holds a positive value on economic growth.